REKONSTRUKSI DAN PERBANDINGAN CERITA RAKYAT KI AGENG MANGIR - , DHANU SETIAWAN; , Dr. Wisma Nugraha Ch. R., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ki Ageng Mangir is a popular folklore in Javanese community, especially in Yogyakarta. Ki Ageng Mangir story passed down between generations orally, especially in regions that have a special relation with the kingdom of Mataram and Ki Ageng Mangir himself. The legend of Ki Ageng Mangir who was the leader of Mangir who oppose the king of Mataram is Panembahan Senopati . The core of this study is the comparison of the reconstructed version the legend of Ki Ageng Mangir from two different areas, then contrasting both of them by using structural theory of narrative by Seymour Chatman. The reconstruction of stories compiled as the results of the interview in Mangir Village as the origin of the story and Pleret as one of the areas considered to be closely related with the Kingdom of Mataram. The results show the differences and similarities between folklore Ki Ageng Mangir of Pleret and Mangir. The similiarity is on the kernel I, II , III , IV , IX , and XI ,especially in the early part of the story. The differences can be seen in the kernel IV , VI , VII , VIII , X , XII , XIII , and XIV. Similarities are found at the beginning of the story. Panembahan Senopati wanted Mangir to succumbs to Mataram, so he drafted a strategy that involves his daughter Pembayun. Ki Ageng Mangir Panembahan Senopoati eventually became his son in law, and must face Mataram. Discrepancies began to appear from Pembayun role, the implementation of the strategy of conquest, and the end of the story related to the funeral of Ki ageng Mangir.